BLU-e: Over-dimension and over-load for vehicle transport mitigation tool at ferry ports - Tampubolon Freddy; Sarjana Sri; Permatasari Meila; Putri Mori Ritonga Virginia (E3S Web of Conferences)
Over-Dimension and Over-Load (ODOL) mitigation in vehicle transportation at ferry ports needs to involve strict inspection and enforcement of regulations at the port, including the use of weighbridge technology and dimensional measurement systems, and training to identify and provide solutions to violations. The study aims to reduce the number of ODOL vehicles and reduce potential losses in both material and immaterial terms by integrating BLU-e and Ferizy. A qualitative approach was applied to detect ODOL vehicles at the port through observation, surveys and interviews in the Land Transportation Management Center (BPTD) VIII Banten area. The results of the study explain the concept of ODOL, dimensional and payload limitations, and the importance of vehicle weighing which plays an important role in reducing the risk of maritime disasters. Tightening ODOL regulations ensures that vehicle loads are in accordance with ship capacity, reducing the risk of maritime accidents that can result in ship sinking and loss of life. Compliance with the rules must be adhered to by all vehicles operating at the ferry port so that the risk of disaster can be significantly reduced, both in terms of transportation safety, infrastructure protection, and emergency response efficiency.